Optimization of Bamboo Bridge Outbound Activities in Shaping the Religious Character of Grade II Students of Madrasah Ibtidaiyah Alam Ya Bunayya Bungo - Uci Rahma Yani; Muhammad Zaki; Siti Khamim (Journal Emerging Technologies in Education, 2026)
This research is motivated by the importance of forming the religious character of Madrasah Ibtidaiyah students from an early age, while in educational practice there are still symptoms of lack of discipline, low responsibility, lack of confidence, and not optimal practice of religious values in daily life. This study aims to describe the implementation of outbound Bamboo Bridge activities, analyze the optimization strategy and integration of religious values, and explain its impact on the formation of religious character of grade II students of Madrasah Ibtidaiyah Alam Ya Bunayya Bungo. This study uses a descriptive qualitative approach with a type of field research. Data was collected through observation, interviews, and documentation of madrasah heads, homeroom teachers of grade II, outbound assistant teachers, students, and parents. The results of the study show that Bamboo Bridge outbound activities can be an effective medium in shaping religious character if carried out through careful planning, intensive teacher mentoring, value reflection, and continuous evaluation. The impact that arises includes increased discipline, courage, responsibility, patience, and social concern of students. Thus, it can be concluded that the optimization of Bamboo Bridge's outbound acBamboo Bridge; Karakter Religius; Madras; Optimalisasi; Outbound. Ativities contributes significantly to the formation of students' religious character through concrete, fun, and meaningful learning experiences.